2011
DOI: 10.2134/jeq2010.0158
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pasture Renovation on Hydrology, Nutrient Runoff, and Forage Yield

Abstract: Proper pasture management is important in promoting optimal forage growth and reducing runoff and nutrient loss. Pasture renovation is a management tool that improves aeration by mechanically creating holes or pockets within the soil. Pasture renovation was performed before manure application (poultry litter or swine slurry) on different pasture soils and rainfall simulations were conducted to identify the effects of pasture renovation on nutrient runoff and forage growth. Renovation of small plots resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…There were no significant differences among tillage treatments with respect to corn silage yield. Previous reports on the effectiveness of aeration in conserving NH 3 -N and therefore corn silage yield have been inconsistent (Gordon et al 2000;De Koff et al 2011;Maguire et al 2011). De Koff et al (2011 found no consistent influence of aeration before manure application on pasture yields.…”
Section: Corn Silage Yield and Qualitymentioning
confidence: 99%
“…There were no significant differences among tillage treatments with respect to corn silage yield. Previous reports on the effectiveness of aeration in conserving NH 3 -N and therefore corn silage yield have been inconsistent (Gordon et al 2000;De Koff et al 2011;Maguire et al 2011). De Koff et al (2011 found no consistent influence of aeration before manure application on pasture yields.…”
Section: Corn Silage Yield and Qualitymentioning
confidence: 99%
“…They attributed this reduction in slot surface area to accumulation of sediment, residues, and manure. DeKoff et al (2011) also noted that beneficial hydrological characteristics due to aeration (5° offset angle) were absent after three months in a permanent pasture setting. DeLaune and Sij (2012) reported that aeration using offset angels of 0°, 2.5°, 5°, 7.5°, and 10° did not reduce runoff volume compared to no-till three months after aeration of a long-term no-till wheat system.…”
Section: Resultsmentioning
confidence: 92%
“…Mechanical soil aeration has been shown to increase macroporosity, saturated hydraulic conductivity, and air permeability and to decrease bulk density in grazing lands (Burgess et al 2000;Drewry et al 2000). Several researchers have also reported decreased runoff volumes and nutrient losses as a result of soil aeration (deKoff et al 2011;Shah et al 2004;Franklin et al 2007Franklin et al , 2011. However, the effect of aeration on soil physical properties and runoff characteristics have been shown to be effective only in the short term, with these characteristics reverting back to nonaerated plots within 3 to 10 months (deKoff et al 2011;Burgess et al 2000;Houlbrooke 1996;Acock et al 2007;Cournane et al 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Soil disturbance associated with grassland renovation should cause a temporary carbon dioxide CO 2 flush from the soil or promote microbial decomposition of SOC, as is the case with tillage in cropland fields Reicosky and Lindstrom, 1995;Reicosky et al, 1997;Ellert and Janzen, 1999 . At the same time, biomass production is increased, or at least maintained, by grassland renovation Velthof et al, 2010;de Koff et al, 2011;Necpalova et al, 2014 , which may increase SOC through plant litter. Most studies to date have investigated the effects of tillage in grassland Eriksen and Jensen, 2001;Grandy and Robertson, 2006;MacDonald et al, 2010;Willems et al, 2011 or land-use change from or to grassland; Post and Kwon, 2000;Conant et al, 2001;McLauchlan, 2006;Katsuno et al, 2010 on SOC or CO 2 exchange.…”
Section: Introductionmentioning
confidence: 99%